Governing for Child-Friendliness? Perspectives on Children as Users Among Swedish and Danish Urban Open Space Managers - Jansson, Märit; Zalar, Alva; Sundevall, Elin Pritzel; Randrup, Thomas B. (Frontiers in Sustainable Cities, 2020)
Despite the acknowledged importance of outdoor environment quality in supporting children's health and well-being, little is known about how contemporary urban open space management caters for children. In this study, Swedish (n = 54) and Danish (n = 25) local governments were surveyed regarding how they manage urban open space for children, e.g., through a child-centered perspective which might include children's perspectives (participation and governance approaches). The results revealed organizational differences and more active consideration of children as urban open space users in Sweden than in Denmark. A general ambition to increase children's participation was reported, but also associated challenges, including budget limitations and lack of knowledge among managers. More ambitious and child-centered urban open space management units work collaboratively and broadly, through governance processes. This includes going beyond conventional structures and perceptions of what are “places for children” and consider all levels of strategic management (policy, tactical, and operational) in developing child-friendly environments within urban open spaces. The large differences between various management units indicates the importance of individual employees' knowledge and dedication, and the value of exchanging knowledge and experiences.